Investigation in the Effect of Applied Voltage and Working Pressure on Some Plasma Parameters in the Positive Column of Dc Glow Discharge - Jassim, Mustafa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Comsol multiphysics software is established to make a simulation that is comparable with experimental device. by utilizing comsol, the positive column domain of direct-current glow discharge with argon is considered for both of different applied voltage and working gas pressure. The calculations are exhibited by using a precise collision cross sections and Townsend coefficients for the argon. The impacts of voltage and pressure on the Debye length, number of particles in Debye sphere and plasma frequency are calculated and graphically delineated. With this regard to the dependence of plasma parameters on the applied voltage and pressure, some of them are found to be compatible with the experimental results, while others are not. For example, the calculations of the COMSOL shows that the electron temperature is not always decreasing with the increase in the applied voltage, and the Debye length does not give a linearly decreasing relationship but rather an exponentially decreasing relationship. Also, the calculations do not reproduce and match the experimental results for the dependence electron density on working pressure at various potentials.